EMBR-16. SURVIVAL OF INFANTS AND YOUNG CHILDREN WITH MALIGNANT BRAIN TUMORS TREATED WITH INTENSIVE INDUCTION AND MYELOABLATIVE CHEMOTHERAPY AND AUTOLOGOUS HEMATOPOIETIC PROGENITOR CELL RESCUE (AUHCR) WITH OR WITHOUT IRRADIATION (XRT) POST-AUHCR. Issue 2 (22nd June 2018) - Chakravartty, Eesha; Malvar, Jemily; Robison, Nathan; Tran, Hung Ngoc; Margol, Ashley; Vasquez, Laura; Wong, Kenneth; Dhall, Girish
Abstract: Avoiding irradiation in infants/young children with malignant brain tumors has been associated with inferior survival. We reviewed medical records of infants/young children with malignant brain tumors diagnosed at our institution between 1991–2015 that completed intensive induction followed by myeloablative chemotherapy/AuHCR and either did or did not receive XRT post-AuHCR. Ninety-nine patients were identified (55 medulloblastoma, 21 PNET, 15 AT/RT, and 8 choroid plexus carcinoma). Twenty-seven of 99 patients received irradiation post-AuHCR and 72 did not. XRT group had 41% of patients with residual tumor post-induction and 44% with disseminated disease versus 18% and 26%, respectively, in no-XRT group. 5-year event-free survival (EFS) and overall survival (OS) for all patients was 63 + 5% and 73 + 5%. 5-year EFS and OS rates for patients receiving XRT post-AUHCR were 69 + 9% and 78 + 8% versus 60 + 6% and 71 + 6%for no-XRT group (p=0.26 and 0.64). For patients with residual tumor post-induction, 5-year EFS was 65 + 14% for XRT group versus 34 + 14% for no-XRT group (p=0.12). For patients with localized disease at diagnosis, 5-year EFS was 86 + 9% in XRT group versus 65 + 7% in no-XRT group (p=0.12). 5-year EFS for patients with disseminated disease in XRT and no-XRT groups was 47%. For medulloblastoma patients, 5-year EFS and OS rates were 65 + 7% and 89 + 10% in XRT group and 67 + 16% and 82 + 6% in no-XRT group. 5-year EFS was 80 + 13% for AT/RT patients in XRT group versus zero in no-XRT group. For infants/young children with malignant brain tumors completing AuHCR, administration of XRT did not provide significant survival advantage, with the exception of AT/RT.